2017
DOI: 10.18203/2349-3291.ijcp20171693
|View full text |Cite
|
Sign up to set email alerts
|

Study of C - reactive protein in neonatal sepsis

Abstract: Background: Sepsis is one of the most common causes of morbidity and mortality in the newborn. Early diagnosis and treatment is vital to improve outcome. Neonatal sepsis in newborn is characterized by paucity of signs and symptoms and is due to invasion and spread through the body of non-pathogenic/ pathogenic & Gram positive / negative organism. It is subtle disease, the general characteristic of bacterial infection in neonatal period are influenced more by response of the infant than the causative organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Gram negative organisms formed the majority of the isolates as compared to Gram positive organisms (65% vs 35% respectively) in the present study. Klebsiella pneumoniae (41%) was the predominant isolate, which correlates with study of Twinkle N Gandhi et al, (2,13). The causative organisms of neonatal sepsis vary with time and place.…”
Section: Positive Predictive Value 74%supporting
confidence: 83%
“…Gram negative organisms formed the majority of the isolates as compared to Gram positive organisms (65% vs 35% respectively) in the present study. Klebsiella pneumoniae (41%) was the predominant isolate, which correlates with study of Twinkle N Gandhi et al, (2,13). The causative organisms of neonatal sepsis vary with time and place.…”
Section: Positive Predictive Value 74%supporting
confidence: 83%
“…Mehrotra reported a study in 2017 to determine the usefulness of CRP for evaluation of neonatal sepsis in tertiary care hospital. [11] He studied on 50 neonates and reported that 34 (68%) had positive CRP while 31 (62%) had positive blood culture. The sensitivity, specificity, PPV, and NPV of CRP were 90.32%, 42.10%, 71.79%, and 72.72%, respectively.…”
Section: Discussionmentioning
confidence: 99%